IoT-Based Smart Fertigation System for Citrus Plants using Fuzzy Logic Control - Ali, Ircham; Adrinoviarini, Adrinoviarini; Banaty, Oka Ardiana; Kamil, Mohammad Insan (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study develops and evaluates an IoT-based smart fertigation system for citrus plants using a fuzzy logic control (FLC) algorithm integrated with an ESP32 microcontroller and wireless sensors. The research aims to address the limitations of conventional fertigation practices that rely on fixed schedules without considering real-time soil and climate conditions, which often result in water inefficiency and nutrient imbalance. The developed system integrates sensors for soil moisture, temperature, and air humidity to automatically regulate irrigation duration through triangular membership functions and a fuzzy inference model consisting of 64 fuzzy rule combinations. Over a 30-day observation period, twelve citrus seedlings aged 3-4 months after grafting were organized into four experimental groups: manual fertigation (MF), manual irrigation (MI), smart fertigation (SF), and smart irrigation (SI). Experimental findings indicated that the smart fertigation system-maintained soil moisture within a more stable range of 40-55%, and plants in the SF group experienced approximately 7 cm greater height and a twofold increase in leaf count compared to manually irrigated ones. The smart fertigation treatment also produced more uniform, greener, and healthier foliage, signifying balanced nutrient uptake. Overall, the IoT–FLC integration provides a more adaptive and eco-efficient irrigation model that promotes sustainable management of water and nutrients in tropical citrus cultivation.